2018
DOI: 10.1037/rmh0000092
|View full text |Cite
|
Sign up to set email alerts
|

Justice involvement and treatment use among rural veterans.

Abstract: Veterans in rural areas and veterans involved in the criminal justice system have experienced less access to, and use of, health care. However, there is limited information on the treatment needs and health care access of justice-involved veterans who live in rural areas. This study used national Veterans Health Administration data from fiscal year 2014 to examine the interactive effect of rural/urban residence and justice involvement on mental health and substance use disorder treatment entry among veterans d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…With regard to linkage, the VA's VJP offices connect justice-involved veterans to health care services through two nationwide programs, Veterans Justice Outreach (VJO) and Health Care for Reentry Veterans (HCRV), with demonstrated effectiveness. 12,61 The VJP offices also work closely with Veterans Treatment Courts, which provide rehabilitation rather than incarceration for criminal justice involvement, in part by linking veteran participants to mental health, substance use, and medical care, as well as housing and employment services. 62 There is little research on the effectiveness of the VTC model and this research is needed, along with investigation of other means by which the legal system could leverage effective treatment modalities for veterans to reduce criminal justice involvement.…”
Section: Building a Research Agendamentioning
confidence: 99%
“…With regard to linkage, the VA's VJP offices connect justice-involved veterans to health care services through two nationwide programs, Veterans Justice Outreach (VJO) and Health Care for Reentry Veterans (HCRV), with demonstrated effectiveness. 12,61 The VJP offices also work closely with Veterans Treatment Courts, which provide rehabilitation rather than incarceration for criminal justice involvement, in part by linking veteran participants to mental health, substance use, and medical care, as well as housing and employment services. 62 There is little research on the effectiveness of the VTC model and this research is needed, along with investigation of other means by which the legal system could leverage effective treatment modalities for veterans to reduce criminal justice involvement.…”
Section: Building a Research Agendamentioning
confidence: 99%
“…35 In another large, national VA study assessing care for substance use disorders overall, living in a rural, relative to an urban area was associated with a higher marginal probability of receiving past-year treatment. 33 Finally, in a national study of VA patients living with HIV, those living in rural areas were less likely to receive AUD specialty addictions treatment than those living in urban areas. 36 The present study builds on these studies as the most extensive examination of differences in receipt of AUD care across rurality in a national sample of patients with AUD receiving care at the VA.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a recent qualitative study among primary care providers (PCPs) practicing in urban and rural Veterans Health Administration (VA) clinics, those practicing in rural areas described a limited knowledge of AUD medications 24 and reported rarely referring patients with AUD to specialty addictions care due to the perceived futility of doing so given a lack of available resources in their communities. 25 Prior studies have explored rural-urban differences in access to care for mental health conditions [26][27][28] and alcohol and drug use disorders 18,[29][30][31][32][33][34] within and outside of the VA in both national and small, non-representative samples. Early studies on rural-urban differences in care for alcohol and drug use disorders found few differences, 31 whereas other studies identified greater access barriers and lower utilization of addictions care in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to substance use services, our results did not demonstrate a substantial rural-urban disparity although utilization trended lower in non-urban areas, which is also generally consistent with prior research. A VHA study from FY2014 showed that rural residence was associated with lower use of substance use services (Finlay, Harris, et al, 2018). Another study demonstrated that while more than one-quarter of the U.S. population resides in rural areas, only 8.9% of all substance use treatment facilities are located in rural counties (Lenardson, 2007).…”
Section: Discussionmentioning
confidence: 99%